A new cancer immunotherapy via simultaneous DC‐mobilization and DC‐targeted IDO gene silencing using an immune‐stimulatory nanosystem. Issue 8 (10th August 2018) - Zhang, Yujuan; Fu, Jiamin; Shi, Yanmei; Peng, Shanshan; Cai, Ying; Zhan, Xuelin; Song, Na; Liu, Yanling; Wang, Zhigang; Yu, Yanrong; Wang, Yifan; Shi, Qiaofa; et al.
Abstract : The activity of negative immune regulatory molecules, such as indoleamine 2, 3‐oxygenase (IDO), significantly attenuates DC (Dendritic cells)‐mediated immunotherapy. We have previously reported that knockdown of IDO using siRNA can reinstall anti‐tumor immunity. However, a DC‐targeted siRNA delivery system for in vivo mobilized DCs remains to be developed, while gene silencing in mobilized DCs for cancer immunotherapy has never been explored. In our study, we developed a novel DC‐targeted siRNA delivery system, man‐GNR‐siIDO, using as a nanocarrier of siRNA specific for IDO (siIDO) and mannose (man) as a guide molecule for targeting DCs. We explored the immunostimulatory man‐GNR‐siIDO nano‐construct in DCs mobilized by Flt3‐L, a receptor‐type tyrosine kinase ligand, for lung cancer immunotherapy. In vivo DC‐targeted gene silencing of IDO resulted in robust anti‐tumor immunity as evidenced by promoting DC maturation, up‐regulating tumor antigen‐specific T‐cell proliferation and enhancing tumor‐specific cytotoxicity. A combinatorial treatment for Lewis Lung Carcinoma (LLC)‐bearing mice, with man‐GNR‐siIDO and Flt3‐L, significantly attenuated tumor growth and delayed tumor formation, suggesting the treatment feasibility of the man‐GNR‐siIDO system in Flt3‐L mobilized DCs in the immunotherapy of lung cancer. Therefore, our study highlights a clinical potential for a first‐in‐class anti‐cancer immunotherapy through simultaneous DC‐mobilization and DC‐targeted gene silencing of IDO with man‐GNR‐siIDO and Flt3‐L treatments. Abstract : What's new? Mobilization of dendritic cells enhances tumor‐specific T cell responses but negative immune regulatory molecules, such as indoleamine 2, 3‐oxygenase (IDO) attenuate dendritic cell‐mediated immunotherapy. Here the authors use simultaneous dendritic cell mobilization and IDO gene silencing via a dendritic cell–targeted siRNA delivery nanosystem to induce robust anti‐lung cancer immunity in vivo. This provides first proof‐of concept that a two‐pronged immunotherapy involving dendritic cells could be clinically relevant for patients with lung cancer.